PENGARUH KOMISARIS INDEPENDEN, FINANCING TO DEPOSIT RATIO, KOMITE AUDIT, LEVERAGE, UKURAN PERUSAHAAN DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA (Studi Empiris Pada Bank Syariah yang Terdaftar di Bursa Efek Indonesia dan Otoritas Jasa Keuangan Tahun 2016 – 2019) - Kardilla Shinta; Surya Adri Satriawan Raja; Hariyani Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine and analyze the effect of independent commissioners, Financing To Deposit Ratio (FDR), audit committee, leverage, company size and managerial ownership on Earnings Management in Islamic Banks Listed on the Indonesia Stock Exchange and the Financial Services Authority in 2016 – 2019. The research was conducted on Islamic Banks Listed on the Indonesia Stock Exchange and the Financial Services Authority in 2016 – 2019. The total population was 28 companies, while the total sample was 28 companies with a data period of 4 years, from 2016 to 2019, so the data to be collected presented as many as 112 data. The sampling method used the purposive sampling method, while the data analysis used multiple linear regression. The results of the study conclude that the variables of Independent Commissioner (X1), Financing To Deposit Ratio (X2), Audit Committee (X3), Leverage (X4), Company Size (X5) and Managerial Ownership (X6) affect earnings management in registered Islamic Banks. on the Indonesia Stock Exchange and the Financial Services Authority in 2016 – 2019.Keywords: Independent Commissioner, Financing To Deposit Ratio, Audit Committee, Leverage, Company Size and Managerial Ownership.